Preparation method of high-purity sulfide solid electrolyte precursor
Patent Information
- Application Number
- CN202611211593.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-27
AI Technical Summary
当碱金属杂质含量超过一定阈值时,会在晶界处形成高阻抗相,导致离子传输受阻,同时可能引发副反应,降低电池的循环稳定性和安全性
本发明所提供的高纯度硫化物固态电解质前驱体的制备方法,其通过结合溶解度调控剂产生的同离子效应以及梯度降温结晶工艺,实现了对Na⁺/Li⁺交换反应过程、成核行为及晶体生长过程的协同调控。其中,梯度降温结晶策略与硫化锂晶种诱导作用相结合,有效促进了目标产物的定向成核与均匀生长,使所得产物具有晶粒细小、粒径分布均一、粒径可控及比表面积较大的特点,有利于后续硫化物固态电解质的高效构筑及电化学性能提升;
Smart Images

Figure CN122977408A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy materials technology, specifically a method for preparing a high-purity sulfide solid electrolyte precursor. Background Technology
[0002] With the global energy structure transformation and the rapid development of the new energy vehicle industry, lithium-ion batteries, as core energy storage devices, are receiving increasing attention for their performance indicators such as safety, energy density, and cycle life. Traditional liquid lithium-ion batteries, which use organic liquid electrolytes, pose safety hazards such as flammability, leakage, and poor thermal stability, severely hindering their widespread adoption in high-energy-density applications. Solid-state electrolytes, on the other hand, are considered a key breakthrough direction for next-generation lithium battery technology due to their non-flammability, leak-proof nature, and good thermal stability.
[0003] Among numerous solid-state electrolyte materials, sulfide solid-state electrolytes have attracted considerable attention due to their ultra-high ionic conductivity (reaching the order of 10⁻² S / cm, approaching or even exceeding that of liquid electrolytes), good mechanical properties, and compatibility with electrode materials. Lithium sulfide (Li₂S), as the core raw material of sulfide solid-state electrolytes, directly determines the electrochemical performance of the final electrolyte material based on its purity. Studies have shown that impurities in lithium sulfide, especially alkali metal impurities (such as sodium and potassium), significantly affect the ionic conductivity, electrochemical window stability, and interfacial compatibility of sulfide solid-state electrolytes. When the content of alkali metal impurities exceeds a certain threshold, a high-resistivity phase forms at grain boundaries, hindering ion transport and potentially triggering side reactions, thus reducing the cycle stability and safety of the battery.
[0004] Currently, the main methods for preparing lithium sulfide include the following: (1) Direct sulfidation: reacting lithium source (such as lithium hydroxide, lithium carbonate) with hydrogen sulfide or elemental sulfur at high temperature. This method has harsh reaction conditions, high energy consumption, and the product is easily oxidized; (2) Solvothermal method: alkali metal sulfides and lithium salts undergo ion exchange reaction in an organic solvent. This method is relatively simple to operate, but there is a serious problem of residual alkali metal ions. In the traditional solvothermal method, a single solvent (such as ethanol, methanol, etc.) is usually used. Because the alkali metal sulfides partially dissolve in the reaction body, the alkali metal impurity content in the generated lithium sulfide product is as high as several thousand ppm, which far exceeds the requirements of practical applications.
[0005] In the prior art, the main methods for reducing alkali metal impurities in lithium sulfide include post-processing such as multiple washing and recrystallization. However, these methods not only increase the complexity and cost of the process, but may also lead to a decrease in product yield and uneven particle size distribution. The solvents used in the washing process may introduce new impurities, further affecting the purity of the product.
[0006] Therefore, developing a lithium sulfide preparation method that can suppress the introduction of alkali metal impurities at the source, while also being simple in process and having a high yield, is of great significance for promoting the large-scale and industrial application of sulfide solid electrolytes. Summary of the Invention
[0007] In view of the problems existing in the prior art, the present invention provides a method for preparing a high-purity sulfide solid electrolyte precursor.
[0008] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: A method for preparing a high-purity sulfide solid electrolyte precursor includes the following steps: (1) Weigh out anhydrous sodium sulfide and anhydrous lithium chloride; (2) A mixed solvent is prepared by mixing a polar protic solvent and an aprotic solvent at a volume ratio of (4-6):(2-6); (3) Under an inert atmosphere, anhydrous sodium sulfide and lithium chloride are added to the mixed solvent of step (2), and a solubility regulator is added to the mixed solvent. Then the complex is added and stirred to obtain the first material. (4) The first material is subjected to gradient cooling, centrifugation after the end, and the supernatant is collected. The supernatant is concentrated under reduced pressure under inert atmosphere. When the system reaches lithium sulfide saturation, lithium sulfide seed crystals are added to induce crystallization. The concentration is continued under reduced pressure to obtain crude product. The crude product is washed and dried to obtain the sulfide solid electrolyte precursor. Furthermore, the gradient cooling conditions are as follows: first, the temperature is reduced from 25℃ to 0℃-15℃ at a rate of 1-3℃ / min, and held for 1-3 hours; then, the temperature is reduced to 10℃ to -20℃ at a rate of 0.5-2℃ / min, and held for 6-12 hours.
[0009] The preparation method of the complex includes the following steps: Weigh out dehydrated PEGDE-1000, menthol, and 2,2-dimethoxypropane, mix them, stir at 45-50℃ for 20-30 min, cool to room temperature, seal and store to obtain the complex. The preparation method of the complex includes the following steps: Weigh out dehydrated PEGDE-1000, menthol and 2,2-dimethoxypropane, mix them, and stir magnetically for 20-30 minutes at 45-50℃. After cooling to room temperature, seal and store to obtain the complex.
[0010] Furthermore, the molar ratio of anhydrous sodium sulfide to anhydrous lithium chloride is 1:(1-2).
[0011] Furthermore, the polar protic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol.
[0012] Furthermore, the aprotic solvent is one or more of tetrahydrofuran, ethylene glycol dimethyl ether, 1,4-dioxane, ethyl acetate, and acetone.
[0013] Furthermore, the solubility regulator is lithium chloride, and the amount of solubility regulator added is 0.5% to 5% of the total mass of the reaction system.
[0014] Furthermore, the amount of the complex added is 0.2%-0.3% of the theoretical product mass.
[0015] Furthermore, the amount of lithium sulfide added is 0.1% to 5% of the theoretical product mass.
[0016] Furthermore, the mass ratio of PEGDE-1000, menthol, and 2,2-dimethoxypropane is (7.5-8):(1-1.5):(1-1.5).
[0017] The present invention also provides a sulfide solid electrolyte precursor prepared by a method for preparing a high-purity sulfide solid electrolyte precursor.
[0018] This invention also provides the application of a high-purity sulfide solid electrolyte precursor in the preparation of sulfide solid electrolytes; the sulfide solid electrolytes include, but are not limited to, Li₂S-P₂S₅, Li₃PS₄, and Li₂S₅. 10 GeP2S 12 One or more of Li6PS5Cl.
[0019] The beneficial effects of this invention include: The method for preparing high-purity sulfide solid electrolyte precursors provided by this invention achieves synergistic regulation of the Na⁺ / Li⁺ exchange reaction process, nucleation behavior, and crystal growth process by combining the common ion effect generated by a solubility regulator with a gradient cooling crystallization process. Specifically, the combination of the gradient cooling crystallization strategy and the induction effect of lithium sulfide seed crystals effectively promotes the directional nucleation and uniform growth of the target product, resulting in a product with fine grains, uniform particle size distribution, controllable particle size, and a large specific surface area. This is beneficial for the efficient construction and improved electrochemical performance of subsequent sulfide solid electrolytes. This invention introduces a complex composed of menthol, 2,2-dimethoxypropane, and polyethylene glycol dimethyl ether-1000 (PEGDE-1000) into the reaction system in situ. This complex promotes uniform crystal precipitation, reduces the probability of water-induced side reactions, and thus improves the stability of the reaction system. It also optimizes the ion transport environment and regulates the crystal growth process, which is beneficial for obtaining products with uniform particle size. The complex provided by this invention can further enhance the ion migration capacity and crystallization control effect in the system, improve the Na⁺ / Li⁺ exchange efficiency and product purity; and the complex exhibits good system compatibility and process adaptability during the reaction.
[0020] The preparation method provided by this invention effectively suppresses impurity ions and regulates crystal growth behavior, significantly reducing the alkali metal impurity content in the obtained product from about 4000 ppm in traditional methods to below 600 ppm, and as low as 320 ppm. This greatly improves the purity of the lithium sulfide precursor and meets the stringent requirements of sulfide solid electrolytes for raw material purity.
[0021] The method provided by this invention can achieve the preparation of high-purity products without relying on complex multi-step washing or recrystallization post-processing. It significantly simplifies the process, reduces production costs, and improves production efficiency. The overall yield can reach more than 85%, and it has good prospects for industrial application and promotion value. Attached Figure Description
[0022] Figure 1 This is a process flow diagram for preparing the sulfide solid electrolyte precursor of the present invention. Detailed Implementation
[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise specified, the reagents of the present invention are all conventional reagents in the art and can be obtained commercially. Unless otherwise specified, the experimental methods used in the present invention are all conventional experimental methods in the art.
[0024] Unless otherwise specified, the raw material processing, reaction and post-processing involved in this invention are all carried out in an anhydrous and oxygen-free environment.
[0025] See attached document Figure 1 This invention provides a method for preparing a high-purity sulfide solid electrolyte precursor.
[0026] Example 1: 1. Preparation method of the complex Weigh 100.0g of PEGDE-1000 and place it in a vacuum drying oven. Dehydrate it at 90℃ and high vacuum for 4 hours to fully remove surface and internal adsorbed moisture. Then transfer it to an argon-protected glove box for later use. In an argon glove box, weigh 8.0 g of dehydrated PEGDE-1000, 1.0 g of menthol (99% purity) and 1.0 g of 2,2-dimethoxypropane, add them to a 50 mL anhydrous beaker and mix thoroughly. Place the mixture on a 45 °C constant temperature heating plate and stir magnetically for 30 min. After the mixture cools naturally to room temperature, seal and store to obtain the complex.
[0027] 2. Preparation method of sulfide solid electrolyte precursor (1) Weigh out 5.1g of anhydrous sodium sulfide (Na2S, analytical grade) and 5.5g of anhydrous lithium chloride (LiCl, analytical grade) for later use; (2) Measure 120 mL of anhydrous ethanol and 80 mL of tetrahydrofuran (THF), mix them evenly to prepare anhydrous ethanol-tetrahydrofuran mixed solvent; (3) In a glove box protected by argon atmosphere, the above anhydrous Na2S and anhydrous LiCl were added to anhydrous ethanol-tetrahydrofuran mixed solvent, and then 0.88g LiCl was added as a solubility regulator; then 7.5mg of the above complex was accurately weighed and added to the above ethanol-tetrahydrofuran mixed solvent, and stirred thoroughly to dissolve it completely to obtain the first material; (4) The first material was placed in a low-temperature constant temperature bath and the temperature was gradually reduced: first, the temperature was reduced from 25℃ to 10℃ at a rate of 2℃ / min and kept for 1h; then the temperature was reduced to 0℃ at a rate of 1℃ / min and kept for 12h; after the reaction was completed, the supernatant was collected at 4000rpm for 10min under 0-4℃ conditions. The supernatant was concentrated under reduced pressure under argon atmosphere. When the system reached Li2S saturation, 0.15g of Li2S seed crystals were added to induce crystallization. The concentration was continued under reduced pressure to obtain the crude product. During the concentration process, the system temperature was controlled not to exceed 30℃. The crude product was washed three times with pre-cooled anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 80℃ for 8h to obtain the sulfide solid electrolyte precursor.
[0028] Example 2: 1. Preparation method of the complex In an argon glove box, 7.5 g of dehydrated PEGDE-1000, 1.0 g of menthol (99% purity) and 1.5 g of 2,2-dimethoxypropane were weighed and added to a 50 mL anhydrous beaker and mixed thoroughly. The mixture was placed on a 45°C constant temperature heating plate and magnetically stirred for 20 min. After the mixture cooled naturally to room temperature, it was sealed and stored to obtain the composite.
[0029] 2. Preparation method of sulfide solid electrolyte precursor (1) Weigh 5.1g of anhydrous Na2S and 2.7g of anhydrous LiCl for later use; (2) Measure 160 mL of anhydrous ethanol and 40 mL of THF, mix them evenly to prepare anhydrous ethanol-tetrahydrofuran mixed solvent; (3) In a glove box protected by argon atmosphere, the above anhydrous Na2S and anhydrous LiCl were added to anhydrous ethanol-tetrahydrofuran mixed solvent, and then 3.36g LiCl was added. 2.94mg of the complex was accurately weighed and added to the above ethanol-tetrahydrofuran mixed solvent. The mixture was stirred thoroughly to dissolve it completely, and the first material was obtained. (4) The first material was placed in a low-temperature constant temperature bath and the temperature was gradually reduced: first, the temperature was reduced from 25℃ to 15℃ at a rate of 1℃ / min and kept for 2h; then, the temperature was reduced to 10℃ at a rate of 0.5℃ / min and kept for 8h; after the reaction was completed, the supernatant was collected at 4000rpm for 15min under 0-4℃ conditions. The supernatant was concentrated under reduced pressure under argon atmosphere. When the system reached Li2S saturation, 44.1mg of Li2S seed crystals were added to induce crystallization. The concentration was continued under reduced pressure to obtain the crude product. During the concentration process, the system temperature was controlled not to exceed 30℃. The crude product was washed three times with pre-cooled anhydrous ethanol and then placed in a vacuum drying oven and dried under vacuum at 80℃ for 8h to obtain the sulfide solid electrolyte precursor.
[0030] Example 3: 1. Preparation method of the complex In an argon glove box, weigh 7.5g of dehydrated PEGDE-1000, 1.5g of menthol (99% purity) and 1.0g of 2,2-dimethoxypropane, add them to a 50mL anhydrous beaker and mix thoroughly. Place the mixture on a 50℃ constant temperature heating plate and stir magnetically for 30min. After the mixture cools naturally to room temperature, seal and store it to obtain the complex.
[0031] 2. Preparation method of sulfide solid electrolyte precursor (1) Weigh 5.1g of anhydrous Na2S and 3.3g of anhydrous LiCl for later use; (2) Measure 120 mL of methanol and 80 mL of ethyl acetate, mix them evenly to prepare a methanol-ethyl acetate mixed solvent; (3) In a glove box protected by argon atmosphere, the above anhydrous Na2S and anhydrous LiCl were added to a methanol-ethyl acetate mixed solvent, followed by the addition of 8.75g LiCl, and then 5.4mg of the complex was accurately weighed and added to the above methanol-ethyl acetate mixed solvent. The mixture was stirred thoroughly to dissolve completely, and the first material was obtained. (4) The first material was placed in a low-temperature constant temperature bath and the temperature was gradually reduced: first, the temperature was reduced from 25℃ to 10℃ at a rate of 2℃ / min and kept for 1h; then the temperature was reduced to 0℃ at a rate of 1℃ / min and kept for 12h; after the reaction was completed, the supernatant was collected at 4000rpm for 15min under 0-4℃ conditions. The supernatant was concentrated under reduced pressure under argon atmosphere. When the system reached Li2S saturation, 36mg of Li2S seed crystals were added to induce crystallization. The concentration was continued under reduced pressure to obtain the crude product. The system temperature was controlled not to exceed 30℃ during the concentration process. The crude product was washed three times with pre-cooled anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 80℃ for 8h to obtain the sulfide solid electrolyte precursor.
[0032] Example 4: 1. Preparation method of the complex In an argon glove box, weigh 8.0 g of dehydrated PEGDE-1000, 1.0 g of menthol (99% purity) and 1.0 g of 2,2-dimethoxypropane, add them to a 50 mL anhydrous beaker and mix thoroughly. Place the mixture on a 45 °C constant temperature heating plate and stir magnetically for 20 min. After the mixture cools naturally to room temperature, seal and store it to obtain the complex.
[0033] 2. Preparation method of sulfide solid electrolyte precursor (1) Weigh 5.1g of anhydrous Na2S and 4.1g of anhydrous LiCl for later use; (2) Measure 80 mL of n-propanol and 120 mL of THF, mix them evenly to prepare a n-propanol-tetrahydrofuran mixed solvent; (3) In a glove box protected by argon atmosphere, the above anhydrous Na2S and anhydrous LiCl were added to the n-propanol-tetrahydrofuran mixed solvent, and then 1.80g LiCl was added. Then, 4.5mg of the complex was accurately weighed and added to the above n-propanol-tetrahydrofuran mixed solvent. The mixture was stirred thoroughly to dissolve it completely, and the first material was obtained. (4) The first material was placed in a low-temperature constant temperature bath and the temperature was gradually reduced: first, the temperature was reduced from 25℃ to 5℃ at a rate of 3℃ / min and kept at that temperature for 3h; then, the temperature was reduced to -10℃ at a rate of 2℃ / min and kept at that temperature for 6h; after the reaction was completed, the supernatant was collected at 4000rpm for 15min under 0-4℃ conditions. The supernatant was concentrated under reduced pressure under argon atmosphere. When the system reached Li2S saturation, 22.46mg of Li2S seed crystals were added to induce crystallization. The concentration was continued under reduced pressure to obtain the crude product. During the concentration process, the system temperature was controlled not to exceed 30℃. The crude product was washed three times with pre-cooled anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 80℃ for 10h to obtain the sulfide solid electrolyte precursor.
[0034] Example 5: 1. Preparation method of the complex In an argon glove box, weigh 8.0 g of dehydrated PEGDE-1000, 1.0 g of menthol (99% purity) and 1.0 g of 2,2-dimethoxypropane, add them to a 50 mL anhydrous beaker and mix thoroughly. Place the mixture on a 45 °C constant temperature heating plate and stir magnetically for 20 min. After the mixture cools naturally to room temperature, seal and store it to obtain the complex.
[0035] 2. Preparation method of sulfide solid electrolyte precursor (1) Weigh 5.1g of anhydrous Na2S and 5.5g of anhydrous LiCl for later use; (2) Measure 120 mL of anhydrous ethanol and 80 mL of ethylene glycol dimethyl ether, mix them evenly to prepare anhydrous ethanol-ethylene glycol dimethyl ether mixed solvent; (3) In a glove box protected by argon atmosphere, the above anhydrous Na2S and anhydrous LiCl were added to the ethanol-ethylene glycol dimethyl ether mixed solvent, and then 5.20g LiCl was added. Then, 5.98mg of the complex was accurately weighed and added to the above ethanol-ethylene glycol dimethyl ether mixed solvent. The mixture was stirred thoroughly to dissolve it completely, and the first material was obtained. (4) The first material was placed in a low-temperature constant temperature bath and the temperature was gradually reduced: first, the temperature was reduced from 25℃ to 0℃ at a rate of 2℃ / min and kept at that temperature for 3h; then, the temperature was reduced to -20℃ at a rate of 2℃ / min and kept at that temperature for 6h; after the reaction was completed, the supernatant was collected at 4000rpm for 10min under 0-4℃ conditions. The supernatant was concentrated under reduced pressure under argon atmosphere. When the system reached Li2S saturation, 15mg of Li2S seed crystals were added to induce crystallization. The concentration was continued under reduced pressure to obtain the crude product. During the concentration process, the system temperature was controlled not to exceed 30℃. The crude product was washed three times with pre-cooled anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 80℃ for 8h to obtain the sulfide solid electrolyte precursor.
[0036] Example 6: 1. Preparation method of the complex In an argon glove box, weigh 8.0 g of dehydrated PEGDE-1000, 1.0 g of menthol (99% purity) and 1.0 g of 2,2-dimethoxypropane, add them to a 50 mL anhydrous beaker and mix thoroughly. Place the mixture on a 45 °C constant temperature heating plate and stir magnetically for 20 min. After the mixture cools naturally to room temperature, seal and store it to obtain the complex.
[0037] 2. Preparation method of sulfide solid electrolyte precursor (1) Weigh 5.1g of anhydrous Na2S and 5.5g of anhydrous LiCl for later use; (2) Measure 120 mL of anhydrous ethanol and 80 mL of 1,4-dioxane, mix them evenly to prepare anhydrous ethanol-1,4-dioxane mixed solvent; (3) In a glove box protected by argon atmosphere, the above anhydrous Na2S and anhydrous LiCl were added to the ethanol-1,4-dioxane mixed solvent, and 7.48g of LiCl was added. 5.98mg of the complex was accurately weighed and added to the above ethanol-1,4-dioxane mixed solvent. The mixture was stirred thoroughly to dissolve it completely, and the first material was obtained. (4) The first material was placed in a low-temperature constant temperature bath and the temperature was gradually reduced: first, the temperature was reduced from 25℃ to 10℃ at a rate of 2℃ / min and kept for 1h; then the temperature was reduced to 0℃ at a rate of 1℃ / min and kept for 12h; after the reaction was completed, the supernatant was collected at 4000rpm for 10min under 0-4℃ conditions. The supernatant was concentrated under reduced pressure under argon atmosphere. When the system reached Li2S saturation, 3mg of Li2S seed crystals were added to induce crystallization. The concentration was continued under reduced pressure to obtain the crude product. During the concentration process, the system temperature was controlled not to exceed 30℃. The crude product was washed three times with pre-cooled anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 80℃ for 8h to obtain the sulfide solid electrolyte precursor.
[0038] The residual Na content in the sulfide solid electrolyte precursors prepared in Examples 1-6 was determined by inductively coupled plasma optical emission spectrometry (ICP-OES) to evaluate the effect of different process conditions on the sodium removal efficiency. Meanwhile, the microstructure and particle structure of the precursors obtained in each example were characterized and analyzed by scanning electron microscopy (SEM), and the results are shown in Table 1.
[0039] Table 1. Particle size and residual Na content of the sulfide solid electrolyte precursors prepared in Examples 1-6
[0040] The results showed that the amount of LiCl, the mixed solvent system, and the gradient cooling conditions all significantly affected the sodium removal efficiency and product yield of the sulfide solid electrolyte precursor. Specifically, Example 1, employing a higher LiCl ratio, an ethanol / THF composite solvent system, and a milder gradient cooling process, effectively promoted Na⁺ / Li⁺ ion exchange and ordered crystal growth, reducing the Na residue in the obtained precursor to 320 ppm and achieving a product yield of 90.6%, demonstrating the best overall performance. In contrast, reducing the amount of LiCl or changing the solvent system led to a decrease in sodium removal efficiency and yield, indicating that the composite inducer-assisted low-temperature ion exchange strategy proposed in this invention can significantly improve the purity and preparation efficiency of the sulfide solid electrolyte precursor.
[0041] Comparative Example 1 The preparation of lithium sulfide using a traditional single-polar protic solvent (ethanol) follows these steps: (1) Weigh 5.1g of anhydrous Na2S and 5.5g of anhydrous LiCl for later use; (2) Measure 200 mL of anhydrous ethanol as the reaction solvent; (3) In a glove box protected by argon atmosphere, anhydrous sodium sulfide and lithium chloride were added to ethanol and magnetically stirred at room temperature for 12 hours. (4) After the reaction is complete, centrifuge to separate the solid product and wash it three times with anhydrous ethanol; (5) The solid product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a sulfide solid electrolyte precursor.
[0042] The Na content in the product was detected by ICP-OES. The results showed that the Na content was about 4200 ppm, which is far below the purity requirement of sulfide solid electrolyte raw materials (<1000 ppm), and cannot meet the actual use requirements.
[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no complex was added in Comparative Example 2, but the other steps were the same.
[0044] The Na content in the product was detected by ICP-OES, and the results showed that the Na content was approximately 850 ppm.
[0045] Experimental Example: To verify the application effect of the precursor prepared in this invention in the synthesis of sulfide solid electrolytes, the sulfide solid electrolyte precursor prepared in Example 1 was used to prepare Li3PS4 solid electrolyte according to the following steps, and compared with Li3PS4 solid electrolyte prepared from lithium sulfide by conventional methods: Weigh 2.0 g of sulfide solid electrolyte precursor and 3.4 g of phosphorus pentasulfide, place them in a planetary ball mill, and ball mill at 500 rpm for 20 h under an argon atmosphere; then heat-treat the ball-milled powder under vacuum at 200 °C for 2 h to obtain Li3PS4 solid electrolyte.
[0046] The ionic conductivity of the Li3PS4 solid electrolyte was measured using electrochemical impedance spectroscopy, and the results showed that the room temperature ionic conductivity was 2.1 × 10⁻⁻⁻⁻⁶. 4 The S / cm ratio is significantly higher than that of Li3PS4 synthesized from lithium sulfide (with a Na content of approximately 4000 ppm) prepared using conventional methods (ionic conductivity of approximately 8 × 10⁻⁻¹). 5 (S / cm). The above results indicate that the sulfide solid electrolyte precursor prepared in this invention can effectively improve the electrochemical performance of the sulfide solid electrolyte.
[0047] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-purity sulfide solid electrolyte precursor, characterized in that, Includes the following steps: (1) Weigh out anhydrous sodium sulfide and anhydrous lithium chloride; (2) A mixed solvent is prepared by mixing a polar protic solvent and an aprotic solvent at a volume ratio of (4-6):(2-6); (3) Under an inert atmosphere, anhydrous sodium sulfide and lithium chloride are added to the mixed solvent of step (2), and a solubility regulator is added to the mixed solvent. Then the complex is added and stirred to obtain the first material. (4) The first material is subjected to gradient cooling, centrifugation after the end, and the supernatant is collected. The supernatant is concentrated under reduced pressure under inert atmosphere. When the system reaches lithium sulfide saturation, lithium sulfide seed crystals are added to induce crystallization. The concentration is continued under reduced pressure to obtain crude product. The crude product is washed and dried to obtain the sulfide solid electrolyte precursor. The gradient cooling conditions are as follows: first, the temperature is reduced from 25℃ to 0℃-15℃ at a rate of 1-3℃ / min, and held for 1-3 hours; then, the temperature is reduced from 10℃ to -20℃ at a rate of 0.5-2℃ / min, and held for 6-12 hours. The preparation method of the complex includes the following steps: Weigh out dehydrated PEGDE-1000, menthol and 2,2-dimethoxypropane, mix them and stir at 45-50℃ for 20-30 min, cool to room temperature, seal and store to obtain the complex.
2. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The molar ratio of anhydrous sodium sulfide to anhydrous lithium chloride is 1:(1-2).
3. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The polar protic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol.
4. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The aprotic solvent is one or more of tetrahydrofuran, ethylene glycol dimethyl ether, 1,4-dioxane, ethyl acetate, and acetone.
5. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The solubility regulator is lithium chloride, and the amount of solubility regulator added is 0.5% to 5% of the total mass of the reaction system.
6. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The amount of the composite added is 0.2%-0.3% of the theoretical product mass.
7. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The amount of lithium sulfide added is 0.1% to 5% of the theoretical product mass.
8. The method for preparing a high-purity sulfide solid electrolyte precursor according to claim 1, characterized in that, The mass ratio of PEGDE-1000, menthol, and 2,2-dimethoxypropane is (7.5-8):(1-1.5):(1-1.5).
9. A high-purity sulfide solid electrolyte precursor, characterized in that, The high-purity sulfide solid electrolyte precursor is prepared according to the method described in any one of claims 1-8.
10. The application of the high-purity sulfide solid electrolyte precursor according to claim 9 in the preparation of sulfide solid electrolytes.